Personalising the technological experience - Charalambous, Andreas (My University, 2021)
The rise of technology has seen an instrumental increase in the field of healthcare across many clinical areas resulting in a change in the face of healthcare. Patient care technology has become increasingly complex, transforming the way healthcare care is conceptualised and delivered. As the future of healthcare is about the patient, there needs to be an alignment of how optimally emerging technology meets the patient's needs. From the patient's point of view, care customisation has always been an important aspect of quality in healthcare. Every patient wants to feel that he/she is getting the care that is tailored to his/her particular needs. This need and desire expressed by the patients extends to include the emerging technologies that are increasingly utilised as part of their care. The challenges of personalising such technologies and the pathways that this can be achieved are presented in this chapter. The chapter presents the conceptual background of the topic followed by the discussion of the main model that can drive the personalisation process in healthcare.
Keywords: Personalisation; Customisation; User needs; Technology; Healthcare